2022
DOI: 10.3390/ma15041384
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Glass-Ceramic Foam from Clay-Rich Waste Diatomaceous Earth

Abstract: In this study, the potential use of waste diatomaceous earth from the production of diatomaceous earth for filtration purposes, as an alternative raw material for foam glass production, was explored. The chemical and mineralogical composition and the high temperature behavior of waste diatomite were studied to assess its suitability for foam glass production. Glass-ceramic foams were prepared using NaOH solution as a foaming agent, via a hydrate mechanism. The influence of different pretreatments and firing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The paper [8] considers a method for manufacturing foam glass using float glass waste and sodium hydroxide. Titanium dioxide TiO 2 was introduced as hardening additive.…”
Section: Introductionmentioning
confidence: 99%
“…The paper [8] considers a method for manufacturing foam glass using float glass waste and sodium hydroxide. Titanium dioxide TiO 2 was introduced as hardening additive.…”
Section: Introductionmentioning
confidence: 99%
“…For example, temperature indices have increased in several countries because of climate change, leading to a growing demand for materials with thermal insulation properties [ 10 , 11 ]. In this context, glass foams have become of great interest to civil construction [ 12 ], as they are chemically inert and non-toxic, present low density, high compression resistance, better thermal insulation [ 13 ], and greater resistance to weather compared to polymeric foams, which can cause serious problems related to fire risk, short service life, and toxicity [ 14 , 15 , 16 , 17 , 18 ]. Temperature is known to have a strong influence on the production of glass foams [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several materials are suitable for manufacturing glass foams, alumina, mullite, silicon carbide, zirconia, and hydroxyapatite. Soda-lime glass accounts for 90% of all glass produced worldwide, and studies have demonstrated the advantages of its application [ 16 ], which can favor the expansion of glass foam (<450%) with the addition of CaCO 3 as a foaming agent [ 13 , 24 , 25 ]. The soda-lime glass can represent 97% of the glass foam mass [ 11 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, diatomite mined from geological deposits must be purified before being used; thermal pre-calcination and HCl washing are the treatments generally used to increase powder quality and to make the biomaterial inert as filter support [ 29 ]. In the construction industry, diatomite finds use in lightweight brick manufacturing [ 30 , 31 ] to produce ceramics [ 32 , 33 , 34 ] for the improvement of MOC composites [ 35 ] and as a part of shape-stabilized phase change materials [ 36 , 37 ]. It is also applied in designing and developing high-temperature resistant and thermal insulation materials [ 38 , 39 ] and as lightweight aggregate manufacturing mortar and concrete [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%